The Institutional Economics of Stakeholder Consultation; Reducing Implementations Costs through 'Matching Zones' - Frank A.G. den Butter; Sjoerd ten Wolde (Tinbergen Institute, 2011)
This paper discusses various ways to organise these consultations, so that a compromise agreement is reached on the solution of the (re)distribution problem. These institutionalised structures of consultation are referred to as 'matching zones' here. Practical experiences, mainly from the Netherlands, provide guidelines for the effective institutional setup of such 'matching zones'. Specifically, the design of a 'matching zone' should try to adhere to the following principles: (i) there should be a common interest and ample incentives for consensus; (ii) there should be the prospect of long, repeated interaction; (iii) there should be a balance between representation and efficiency; (iv) the constraints should be clear from the onset of the matching zone; (v) fairness should be strived for; (vi) IC technology should be utilised optimally; and (viii) informal contacts and an amicable atmosphere should be promoted.
urn:NBN:nl:ui:31-1871/38569
Keywords: D23; D63; D74; H11; 330; Institutional economics; G2B and G2C relationship; public-private cooperation; transaction costs; regulatory pressure; matching zone